Reforming the Stability and Growth Pact - Annett, Anthony (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2005)
A rules-based fiscal framework, such as the EU's Stability and Growth Pact (SGP), can be an important bulwark against short-sighted policies. Although policies have improved following the SGP's adoption, shortcomings remain. These, however, are rooted in the policies rather than the rules, where few changes seem necessary. Specifically, the Excessive Deficit Procedure needs a stronger focus on policies rather than outcomes, while staying operationally simple and transparent. Furthermore, reforms are needed to foster time-consistent national policies, budgetary transparency, and ownership of the Pact. Accordingly, parliaments should debate national Stability Programs and national fiscal councils should review these programs for parliaments.